CONTINUITY IN THE EDUCATIONAL PROCESS - A FACTOR IN THE TRAINING OF DOG SPECIALISTS - Mohinur, Bafo (Confrencea, 2022)
The effective work carried out within the framework of the third initiative is gaining importance in increasing the computer literacy and intellectual potential of young people. Interest in the use of innovative technologies in the educational system and attention to the introduction of modern methods are increasing day by day. The reason is that earlier the educational goal was focused on the acquisition and memorization of ready-made knowledge.